Konstruksi Sosial Eksistensi Danantara pada Nasabah Bank Negara Indonesia Cabang Denpasar - Ni Nyoman Sintha Tresnawati; Ni Wayan Widhiastini (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2026)
The establishment of the Daya Anagata Nusantara Investment Management Agency (Danantara) in 2025 triggered the spread of misinformation regarding the management of funds in state-owned banks, including Bank Negara Indonesia (BNI). The lack of early public communication led some BNI Denpasar Branch customers to experience uncertainty and concern about the security of their savings. This study aims to analyze the role of BNI’s organizational communication in shaping customers’ social construction of Danantara’s existence through Berger and Luckmann’s three stages of social construction, externalization, objectivation, and internalization. This research employs a descriptive qualitative approach using in-depth interviews, observation, and documentation involving customers, frontliners (customer service and tellers), and supporting informants from GenBI, totaling seven participants. The findings show that in the externalization stage, customers’ initial perceptions were shaped by social media information dominated by negative and speculative narratives. In the objectivation stage, BNI’s organizational communication, through internal briefings, circular letters, and direct clarification by frontliners, played a role in stabilizing meanings and reducing customer anxiety. In the internalization stage, customers accepted a new understanding that Danantara is not related to their deposits, allowing them to regain a sense of financial security. Thus, BNI’s organizational communication plays a significant role in shaping customers’ social construction, dispelling misinformation, and restoring public trust in the bank’s stability amid national issues related to Danantara.